A composite indicator of financial conditions for Germany - Norbert Metiu (Deutsche Bundesbank, 2022)
This paper proposes a composite indicator of financial conditions for Germany. The composite indicator distills information from large amounts of data covering different segments of the German financial system into a summary measure of financial conditions. This measure is constructed from 70 individual financial indicators for the period between January 2003 and June 2022. The findings show that there were four main episodes of tight financial conditions in Germany, which coincide with the financial crisis of the early 2000s, the 2008 global financial crisis, the euro area sovereign debt crisis of the early 2010s and the COVID-19 recession in 2020. Recent readings of the composite indicator point to tighterthan- average financial conditions in the first half of 2022. Estimates from a structural vector autoregression indicate that financial shocks account for a relatively large part of the variation in financial conditions, while macroeconomic shocks play a smaller role.
Keywords: E44; E51; G12; G17; 330; diffusion index; factor model; financial conditions; financial stability